Macular Telangiectasia type 2: multimodal assessment of retinal function and microstructure. Issue 6 (1st December 2021) - Ledolter, Anna A.; Ristl, Robin; Palmowski‐Wolfe, Anja M.; Montuoro, Alessio; Deak, Gabor G.; Sacu, Stefan; Holder, Graham E.; Schmidt‐Erfurth, Ursula; Ritter, Markus
Abstract: Purpose: To assess the impact of neurodegenerative morphologic alterations due to macular telangiectasia type 2 (MacTel) on microperimetry (MP) and multifocal electroretinography (mfERG). Methods: Thirty‐five eyes of 18 patients with MacTel were examined using spectral domain optical coherence tomography (SD‐OCT), fundus autofluorescence (FAF), mfERG and MP. Software was used to match SD‐OCT B‐scans with the corresponding retinal sensitivity map and multifocal electroretinograms (mfERGs), thus enabling direct structure/function correlation. Results: Loss of the ellipsoid zone (EZ) had the strongest negative association with retinal sensitivity (16.77 dB versus 4.58 dB, adj. p < 0.001) of all parameters examined, and a limited negative effect on mfERGs (0.32 SD versus −1.97 SD adj. p = 0.121). Ellipsoid zone (EZ) irregularity was associated with reduced MP values but preserved mfERGs. There was a significant association between areas of inner retinal hyporeflectivity and loss of MP sensitivity (adj. p < 0.001) but the reduction in sensitivity was less than in locations with EZ loss. Areas of mfERG abnormality showed similar sensitivity loss with either inner retinal hyporeflectivity or EZ loss (adj. p = 0.063). In areas with EZ loss alone, preservation of the external limiting membrane (ELM) was associated with higher MP values than in areas with additional ELM loss; the integrity of the ELM alone was not associated with changes either in MP or mfERG. Increased FAF was observed in 51% of eyes, mixed/reduced FAF in 40%, and no abnormality was detected in 9% of eyes. Conclusion: The data suggest both MP and mfERG to be useful non‐invasive modalities for detecting localised macular dysfunction in MacTel. The findings suggest a different sensitivity of the two modalities to inner and outer retinal changes in macular function and are therefore complementary.